China's Space Policy Towards the United States in the Background of Global Public Domain Coping with - Cao, Jingyue (International Journal of Social Sciences and Public Administration, 2025)
With the progress of science and technology, the deepening degree of globalization, space policy also appear new situation -- global public domain, the new situation shows that the new attitude in the field of space, our country under this new situation bright Ming own point of view, with a positive attitude to respond to the new policy, clear China always adhere to and develop the "human destiny community" this concept to promote our space policy.